The Effects of Vitamin D Supplementation on Signaling Pathway of Inflammation and Oxidative Stress in Diabetic Hemodialysis: A Randomized, Double-Blind, Placebo-Controlled Trial - Haddad Kashani, Hamed; Seyed Hosseini, Elahe; Nikzad, Hossein; Soleimani, Alireza; Soleimani, Maryam; Tamadon, Mohammad Reza; Keneshlou, Fariba; Asemi, Zatollah (Frontiers in Pharmacology, 2018)
Objective: This study was carried out to determine the effects of vitamin D supplementation on signaling pathway of inflammation and oxidative stress in diabetic hemodialysis (HD) patients. Methods: This randomized double-blind placebo-controlled clinical trial was conducted among 60 diabetic HD patients. Subjects were randomly allocated into two groups to intake either vitamin D supplements at a dosage of 50,000 IU (n=30) or placebo (n=30) every 2 weeks for 12 weeks. Gene expression of inflammatory cytokines and biomarkers of oxidative stress were assessed in peripheral blood mononuclear cells (PBMCs) of diabetic HD patients with RT-PCR method. Results: Results of RT-PCR indicated that after the 12-week intervention, compared to the placebo, vitamin D supplementation downregulated gene expression of interleukin (IL)-1β (P=0.02), tumor necrosis factor alpha (TNF-α) (P=0.02) and interferon gamma (IFN-γ) (P=0.03) in PBMCs of diabetic HD patients. Additionally, vitamin D supplementation, compared to the placebo, downregulated gene expression of transforming growth factor beta (TGF-β) (P=0.04), protein kinase C (PKC) (P=0.001) and mitogen-activated protein kinases 1 (MAPK1) (P=0.02) in PBMCs of diabetic HD patients. Finally, vitamin D supplementation let to a non significant reduction in nuclear factor kappa B (NF-κB) (P=0.75) in PBMCs of diabetic HD patients compared to the placebo. There was no statistically significant change following supplementation with vitamin D on gene expression of interleukin (IL)-4, IL-6 and vascular endothelial growth factor (VEGF) in PBMCs of diabetic HD patients. Conclusions: Overall, we found that vitamin D supplementation for 12 weeks among diabetic HD patients had beneficial effects on few gene expression related to inflammation and oxidative stress. Clinical trial registration: IRCT201701035623N101. Registered on January 8, 2017.